2022
DOI: 10.1177/10760296221119807
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Hematologic Characterization of Thalassemia in Guangdong Province, Southern China

Abstract: Introduction: About 2% of the population in the world are carriers of the thalassemia gene. Thalassemia is highly prevalent in Southern China, and traditional clinical testing methods would cause missed diagnosis of partial static thalassemia. Here, we reviewed and summarized a set of simple and clinically feasible thalassemia detection protocols adopted by the Prenatal Diagnosis and Reproductive Center of our hospital. Methods: From January 1, 2015, to December 31, 2020, 31 512 peripheral blood samples and 38… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 34 publications
(32 reference statements)
2
4
0
Order By: Relevance
“…Our study revealed a high TT prevalence in South China. It is consistent with the literature reported 18 . The high prevalence of TT in South China 1,19 underscores the significance of TT carrier screening in this region 3,6 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study revealed a high TT prevalence in South China. It is consistent with the literature reported 18 . The high prevalence of TT in South China 1,19 underscores the significance of TT carrier screening in this region 3,6 .…”
Section: Discussionsupporting
confidence: 92%
“…It is consistent with the literature reported. 18 The high prevalence of TT in South China 1,19 underscores the significance of TT carrier screening in this region. 3,6 The --SEA /αα and α 3.7 /αα genotypes showed the highest proportions in α-TT, while β CD41-42 /β N and β (IVS-II-654) /β N exhibit the highest proportions in β-TT.…”
Section: Discussionmentioning
confidence: 99%
“…The most common gene mutation for the β‐thalassemia was found to be β CD17(A>T) , which is consistent with studies conducted in Yunnan and previous results from Guizhou [ 17 , 24 ]. In Hubei and Fujian [ 2 , 25 , 26 ], the most common mutation associated with β‐thalassemia is β IVS‐II‐654 /β N , whereas in Guangdong [ 27 , 28 ], Guangxi [ 29 ], Sichuan [ 30 ], and Hainan [ 22 ] (Table 4 ), the predominant mutation is β CD41‐42 (‐TCTT) /β N . However, in certain regions, such as Zunyi, Anshun, Qianxinan, and Qiannan, the highest prevalence of the β‐thalassemia genotype is β CD41‐42 (‐TCTT) , possibly due to variations in the distribution of ethnic minorities.…”
Section: Discussionmentioning
confidence: 99%
“…More than 200 types of β-thalassemia gene mutations have been found at home and abroad, covering the promoter region, exon region, cut region, and 3’ untranslated region of the HBB gene. Epidemiological studies have demonstrated that there are significant geographical and ethnic differences in the types of gene mutations [ 7 , 31 , 32 ]. For example, HBB :c.79G>A carries 50% in India in South Asia, whereas it carries 0.1% in Pakistan [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 46 β-thalassemia mutations have been reported in the Chinese populations. Eight types, including HBB :c.126_129delCTTT, HBB : c.316-197C>T, HBB : c.216_217insA, HBB : c.52A>T, HBB : c.-78A>G, HBB : c.79G>A, HBB : c.-79A>G, HBB : c.130G>T accounted for more than 95% of the total number of β-thalassemia [ 7 , 31 , 34 ]. On this basis, our group designed a probe capture panel with 12 gene mutation types, including the eight mutations mentioned above, to meet the epidemiological and clinical needs.…”
Section: Discussionmentioning
confidence: 99%